Physiological changes in sugarcane in function of air and ground application of fungicide for orange rust control (Bioscience Journal, 2018)
The application of fungicides in different operating conditions is a usual practice for maintaining the productive potential in sugarcane varieties considered susceptible to orange rust, however, the physiological effects provided by the different application methods are unknown. The objective of this study was to evaluate the photosynthetic responses (gas exchange and chlorophyll content) in the SP81-3250 sugarcane variety, in function of different operational conditions of the aerial and ground application of fungicide in the orange rust control. Two application of fungicides of the chemical groups Strobilurins and Triazoles were carried out in the experimental units in different treatments. In the aerial applications, two application rates (30 and 40 L ha-1) and three nozzle orientations (0º, 90º and 135º) and in the ground application was used 200 L ha-1 and flat fan spray nozzles with air induction (AI11004-VS). Gas exchange evaluations were performed with an IRGA and amount of chlorophyll a and b with a chlorophyll meter. Data were analyzed using Student's t-test for independent samples, at 0.05 significance. The aerial application provided better photosynthetic responses and chlorophyll a and b contents in leaf limb compared to ground application. Significant differences were detected in gas exchange and chlorophyll content between application rates and angulation of the spray nozzles in the boom. Fungicide applications provided increments of more than 19 t ha-1 compared to the control, depending on the spraying technique employed. Aerial application with 30 L ha-1 and 0° of deflection is a viable option to provide safer applications as a function of the larger droplet size.